FACTORS AFFECTING PURCHASE INTENTION OF THE ICE CREAM INDUSTRY - Tjayadi, Stefanni; Tjokrosaputro, Miharni; Ariniputri, Nadia (International Journal of Application on Economics and Business, 2023)
The contemporary beverage business has recently begun attracting much attention from Indonesian consumers, especially in Jakarta. The contemporary beverage industry has recently garnered significant attention among consumers in Jakarta, Indonesia. This investigation aimed to ascertain whether there is a relationship between Electronic Word of Mouth (E-WOM) and Perceived Price with respect to customer Purchase Intention for ice cream, with Trust serving as a mediating factor. The study's participants were residents of Jakarta, with a sample size of 225 individuals selected through purposive sampling. Data analysis was conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique. The findings of this research reveal that E-WOM, perceived price, and trust influence consumer purchase intentions for ice cream products in Jakarta. Furthermore, this study highlights the mediating role of trust in the relationship between E-WOM and consumer purchase intentions.